Axiological Insights into Unveiling Independent Constitutional Judge Decisionism - Artha Debora Silalahi; Rizal Mustansyir; Sindung Tjahyadi; Septiana Dwiputri Maharani (Yustisia, 2024)
This study analyzeshow axiological principles such as justice, utility, and justice influence judicial decisions and impact the credibility and effectiveness of the legal system. Critically analyzing case studies and theoretical perspectives examines the interplay between judicial independence and accountability. The article emphasizes the role of values in shaping laws, advocating for consistency and consideration of consequences in judicial decision-making. It argues that moral and ethical principles are central to judicial discretion, ensuring that decisions align with societal values and legal integrity. This nuanced analysis contributes to the discourse on how value-driven decision-making enhances the coherence and legitimacy of the legal system, offering insights into the balance between judicial autonomy and responsibility